Digital Closed-Loop Driving Technique Using the PFD-Based CORDIC Algorithm for a Biaxial Resonant Microaccelerometer. (26th October 2017) - Yang, Bo; Wu, Lei; Wang, Binlong; Wang, Qiuhua
Abstract : A digital closed-loop driving technique is presented in this paper that uses the PFD- (phase frequency detector-) based CORDIC (coordinate rotation digital computer) algorithm for a biaxial resonant microaccelerometer. A conventional digital closed-loop self-oscillation system based on the CORDIC algorithm is implemented and simulated using Simulink software to verify the system performance. The system performance simulations reveal that the incompatibility between the sampling frequency and effective bits of AD and DA convertors limits further performance improvements. Therefore, digital, closed-loop self-oscillation using the PFD-based CORDIC algorithm is designed to further optimize the system performance. The system experimental results illustrate that the optimized system using the PFD-based CORDIC improves the bias stability of the resonant microaccelerometer by more than 5.320 times compared to the conventional system. This demonstrates that the optimized digital closed-loop driving technique using the PFD-based CORDIC for the biaxial resonant microaccelerometer is effective.